1994
DOI: 10.1117/12.177353
|View full text |Cite
|
Sign up to set email alerts
|

<title>Dynamic sine wave response measurements of CRT displays using sinusoidal counterphase modulation</title>

Abstract: 7 18 :013Approvd for pub5c re,•m; dietbuton uimtahd. United States Army Aeromedical Research LaboratoryFort Rucker, Alabama 36362-0577 Oualified reauestersQualified requesters may obtain copies from the Defense Technical Information Center (DTIC), Cameron Station, Alexandria, Virginia 22314. Orders will be expedited if placed through the librarian or other person designated to request documents from DTIC. Chanae of addressOrganizations receiving reports from the U.S. Army Aeromedical Research Laboratory on aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…But, because the rate of the beam sweep in CRTs is a constant, moving that target across frames in dynamic imagery will not greatly effect the contrast already available at a particular spatial frequency (unless the phosphor is inordinately slow as shown in Figure 4-70). This was demonstrated in a study by Verona et al (1994) using temporally modulated sine waves as generic dynamic imagery (undergoing sinusoidal counterphase modulation). They tested two CRTs, with a slow phosphor (P-1) and a fast phosphor (P-44), and found the expected spatial MTF curve, which is the reduction in contrast for higher spatial frequencies.…”
Section: Differences In Image Gray Scales and Contrast In Crts And Fpdsmentioning
confidence: 99%
See 4 more Smart Citations
“…But, because the rate of the beam sweep in CRTs is a constant, moving that target across frames in dynamic imagery will not greatly effect the contrast already available at a particular spatial frequency (unless the phosphor is inordinately slow as shown in Figure 4-70). This was demonstrated in a study by Verona et al (1994) using temporally modulated sine waves as generic dynamic imagery (undergoing sinusoidal counterphase modulation). They tested two CRTs, with a slow phosphor (P-1) and a fast phosphor (P-44), and found the expected spatial MTF curve, which is the reduction in contrast for higher spatial frequencies.…”
Section: Differences In Image Gray Scales and Contrast In Crts And Fpdsmentioning
confidence: 99%
“…MIL-A-49425 (CR) states that distortion shall be no greater than 4 percent across the field-of-view. Martin et al, (1994) found distortion values less than 2 percent.…”
Section: Anvis Optical Specificationsmentioning
confidence: 99%
See 3 more Smart Citations